Foliar-Applied Glutathione Mitigates Cadmium-Induced Oxidative Stress by Modulating Antioxidant-Scavenging, Redox-Regulating, and Hormone-Balancing Systems in Brassica napus - Jung, Ha-il; Lee, Tae-Gu; Lee, Jinwook; Chae, Mi-Jin; Lee, Eun-Jin; Kim, Myung-Sook; Jung, Goo-Bok; Emmanuel, Amoakwah; Jeon, Sangho; Lee, Bok-Rye (Frontiers in Plant Science, 2021)
The antioxidant glutathione (GSH) mitigates adverse physio-metabolic effects and defends against abiotic stress, including cadmium (Cd) stress. However, its function and role in resisting Cd phytotoxicity by plant antioxidant-scavenging, redox-regulating, and hormone-balancing systems have not been comprehensively and systematically demonstrated in the Cd-hyperaccumulating plant Brassica napus L. cv. Tammi (oilseed rape). In this study, the effects of exogenously-applied GSH to the leaves of B. napus seedlings exposed to Cd (10 µM) were investigated. Cd stress alone significantly inhibited growth and increased levels of reactive oxygen species (ROS) and bioaccumulation of Cd in the seedlings compared with that of controls. Furthermore, Cd stress induced an imbalance in plant stress hormones and a decrease in endogenous GSH levels and GSH redox ratios, which were correlated with reductions in ascorbate (AsA) and/or NADPH redox states. However, exogenous application of GSH to Cd-stressed B. napus seedlings reduced Cd-induced ROS levels and enhanced antioxidant-scavenging defenses and redox regulation by both increasing seedling AsA, GSH, and NADPH content and rebalancing stress hormones, thereby enhancing Cd uptake and accumulation. These results demonstrated that GSH improved plant redox status through up-regulating the AsA-GSH-NADPH cycle and reestablishing the normal hormonal balance. This indicates that exogenously applied GSH can mitigate Cd phytotoxicity in B. napus and possibly other plants, and potentially be applied to plant remediation of Cd-polluted soil.